Effects of area, aspect ratio and orientation of rectangular nanohole on the tensile strength of defective graphene – a molecular dynamics study. Issue 31 (9th May 2018) - Qin, Xinmao; Yan, Wanjun; Guo, Xiaotian; Gao, Tinghong
Abstract : Molecular dynamics simulations with AIREBO potential are performed to investigate the effects of rectangular nanoholes with different areas, aspect ratios (length/width ratios) and orientations on the tensile strength of defective graphene. Abstract : Molecular dynamics simulations with adaptive intermolecular reactive empirical bond order (AIREBO) potential are performed to investigate the effects of rectangular nanoholes with different areas, aspect ratios (length/width ratios) and orientations on the tensile strength of defective graphene. The simulations reveal that variation of area, aspect ratio and orientation of rectangular nanohole can significantly affect the tensile strength of defective graphene. For example, defective graphene with a larger area of rectangular nanohole shows a bigger drop in tensile strength. It was found that the tensile strength of both armchair and zigzag edged graphene monotonically decreases with area increases in rectangular nanohole. Changes in aspect ratio and orientation of rectangular nanohole, however, can either decrease or increase the tensile strength of defective graphene, dependent on the tensile direction. This study also presents information that the tensile strength of defective graphene with large area of nanohole is more sensitive to changes in aspect ratio and orientation than is defective graphene with small area of nanohole. Interestingly, variation of tensile strength of defective graphene from MD simulations is in good agreement with predictions from energy-based quantized fracture mechanics (QFM). The present results suggest that the effect of nanoholes on the tensile strength of graphene provides essential information for predictive optimization of mechanical properties and controllable structural modification of graphene through defect engineering.